Basic immunology functions and disorders of the immune system - Abbas, Abul K; Lichtman, Andrew H; Pillai, Shiv (Elsevier, 2014)
Understand all the essential concepts in immunology with this book that provides you with an up-to-date, accessible introduction to the workings of the human immune system. This book enables you to efficiently master the immunology information you need through clinically focused content, logically organized by mechanism. You can apply what you have learned to real-world situations by referencing the appendix of clinical cases. It can enhance your learning with the help of numerous full-color illustrations and useful tables, as well as summary boxes, review questions, and a glossary of immunology terms